METHODOLOGICAL JUSTIFICATION FOR THE PROCESS OF RESTORATION WORK TO STRENGTHEN THE STRUCTURES OF ARCHITECTURAL MONUMENTS (British Journal of Global Ecology and Sustainable Development, 2023)
This article describes the methodological justification for the process of restoration work to strengthen the structures of architectural monuments. This is a good program for researchers in this direction.